Unemployment Durations of French Young People: the Impact of Individual, Family and other Factors on the Hazard Rate - Anna Cristina D'Addio (Tinbergen Institute, 1998)
This paper is concerned with the analysis of the determinants of unemploymentdurations of French Young People. The data used are extracted from the EnqueteEmploi 1990-1992 and the Module Jeunes 1992, both carried out by INSEE.A reduced form approach has been adopted and it is based on the estimation of adiscrete-time hazard model which derives from the extension of the Cox model(1972) as in Prentice and Gloecker (1978). The baseline rate is piecewiseconstant in each interval of two months. A discrete-time hazard model withunobserved heterogeneity has been estimated, too. In it the unobservedheterogeneity has been modelled by means of a gamma distribution.Estimations have been performed separately on men and women durations. Various explanatory variables have beenintroduced in the analysis; they are significant in most cases, but their effects vary according the population ofreference. The conditions to access the labour market will then seem to be very different for the two groups studied.Only the education level and the french nationality of the individual's father have a positive effect on the hazard rate ofboth the two subgroups studied. It is also worthwhile to remark that the variables introduced to take account for thedate of entry in the unemployment spell, have a significant negative effect on the probability of leaving unemploymentboth for men and women showing that this is very sensitive to the economic situation.
Keywords: 330; Jugendarbeitslosigkeit; Frankreich